Geographic relationship between social vulnerability index and dengue transmission: a case study in Praia Grande, São Paulo (Revista Espinhaço, 2018)
Dengue is a worldwide public health problem, usually related to socioeconomic and environmental factors. In Brazil, urban areas without sanitation, high population density (areas of social vulnerability) and climate (tropical and subtropical) create the ideal conditions for the dengue vector proliferation. The goal of this study was to analyze the spatial relationship between dengue transmission and the social vulnerability indexes of the city of Praia Grande in 2010. For this purpose, we analyzed the autochthonous cases confirmed by laboratory and clinical-epidemiological criteria (reporting system of notification), socioeconomic census data (IBGE) and the São Paulo social vulnerability index (SEADE Foundation). Our results relate the high incidence of dengue to census sectors with indicators of medium and high social vulnerability, high population density and good infrastructure and sanitation services. We confirm previous research, showing that the dengue cases concentration occurs in the economically active population (age range of 20-39 years) and female population. We have contributed to the literature showing that the dengue cases distribution occurs independently of social vulnerability, instigating new research on the causal relationships between dengue and geographic space.
Keywords: Dengue transmission; socioeconomic data; reporting system of diseases; social vulnerability index